Interposition versus transposition technique in microvascular decompression for trigeminal neuralgia secondary to vertebrobasilar dolichoectasia: a systematic review and pooled meta-analysis - Signorelli, Francesco; Zeoli, Fabio; Rastegar, Valid; Beccia, Flavia; Caronna, Riccardo; Visocchi, Massimiliano (Frontiers in Neurology, 2024)
IntroductionLimited data are available comparing the interposition and transposition techniques for microvascular decompression (MVD) in patients with trigeminal neuralgia (TN) secondary to vertebrobasilar dolichoectasia (VBD); this study aims to review current findings on TN associated with VBD and compare the interposition and transposition techniques in terms of surgical morbidity and patient outcomes.MethodsFollowing the PRISMA guidelines, PubMed/Medline, Web of Science, and SCOPUS databases were searched to identify studies reporting patients undergoing MVD for TN secondary to VBD. The studies were divided into two groups, interposition and transposition, based on the microvascular decompression technique used. Studies not reporting the diagnostic criteria, included less than five cases, or were not available in English were excluded.ResultsFourteen eligible papers were retrieved, of which five studies reported cases undergoing the interposition technique, eight studies for the transposition technique, and one study reported cases from both groups. Data including preoperative and postoperative BNI class, comorbidities, and postoperative complications were retrieved to analyze and compare the two techniques in terms of efficacy and long-term outcomes in treating TN secondary to VBD.ConclusionBoth interposition and transposition techniques for MVD yield high rates of pain relief in patients with TN secondary to VBD. While both approaches demonstrate similar efficacy, the interposition method is associated with a lower rate of long-term complications. Further research, preferably through randomized prospective studies, is needed to refine surgical strategies and improve patient outcomes.